Liberation enhancement and copper enrichment improvement for waste printed circuit boards by heating pretreatment. (1st April 2020) - Yan, Guanghui; Guo, Junwei; Zhu, Guangqing; Zhang, Zhenxing; Zhao, Pengfei; Xiangnan, Zhu; Zhang, Bo
Graphical abstract: Highlights: Mechanism for weaken-crushing process and fracture mode is expressed. The proper treated conditions and crushing effect reflected on the treated conditions are obtained. The enrichment effect is revealed by analysis of copper grade and yield. The liberation comparison is conducted for treated and untreated crushed products. Abstract: Crushing is the key part for the recycling technology of waste printed circuit boards (WPCBs). In this study, the breakage and liberation effects of WPCBs was improved by heat pretreatment technology before crushing (HPBC). Based on the test results, 200 °C was found as the safe temperature for the HPBC of WPCBs. The fracture mode, particle size distribution, and enrichment characteristics of WPCBs were systematically studied. The experimental results show that the HPBC changed the breakage mode from longitudinal fracture to horizontal fracture and improved the liberation of metal from non-metal components. During the crushing process, the increase in the heat pretreatment time (30–120 min) and temperature (100–200 °C) can improve the crushing effect of WPCBs and increase the content of crushing products of −0.3 mm by 3.16% and 5.64%, respectively. Compared to the non-metallic components, the metal components have ductility and are difficult to break into −0.3 mm during the crushing process. HPBC can promote copper enrichment to narrow grain size. In the 0.3–1 mm range, the content of copper increased from 47.87% to 57.61%, an increase by 9.74%. The initial enrichment of copper was achieved by adjusting the crushing time. The recovery rate of copper can reach 85.66%, and the enrichment rate is 1.74 when 0.3–2 mm breaking product is used as enrichment. Therefore, HPBC can effectively improve the crushing and liberation effect of WPCBs and improve the enrichment rate, and thus is an effective pretreatment method.